2009
DOI: 10.1677/joe-08-0552
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of genistein aglycone on the development of osteonecrosis of the femoral head and secondary osteoporosis induced by methylprednisolone in rats

Abstract: Glucocorticoid (GC)-induced osteoporosis (GIO) is the most important secondary cause of bone loss. Clinical evidence suggests a role for genistein (GEN) aglycone in the prevention of osteoporosis. We investigated whether GEN could prevent GIO as well as the development of osteonecrosis in the femoral head using an experimental rat model. A total of 28 female SpragueDawley rats were used in the study. GIO and osteonecrosis were induced by daily s.c. injections of 30 mg/kg of methylprednisolone (MP; nZ7). Anothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 52 publications
0
49
1
Order By: Relevance
“…We hypothesize that Ovx increases the production of CD4 + CD28null premature senescent cells, and these cells secrete inflammatory cytokines like TNF-α which in turn enhance bone resorption. Additionally, phytoestrogens confer substantial benefits to bone health without posing the risk of cancer associated with HRT [19,20]. Recently, we have shown bone conserving effect of medicarpin (Med), a pterocarpantype phytoalexin present in dietary legume, in Ovx mice, suggesting its E2-"like" effect on bone.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesize that Ovx increases the production of CD4 + CD28null premature senescent cells, and these cells secrete inflammatory cytokines like TNF-α which in turn enhance bone resorption. Additionally, phytoestrogens confer substantial benefits to bone health without posing the risk of cancer associated with HRT [19,20]. Recently, we have shown bone conserving effect of medicarpin (Med), a pterocarpantype phytoalexin present in dietary legume, in Ovx mice, suggesting its E2-"like" effect on bone.…”
Section: Introductionmentioning
confidence: 99%
“…In our study (Figure 1), genistein succeeded in preventing osteoporosis and osteonecrosis of the femoral head when co-administered with the glucocorticoid. The isoflavone statistically maintained bone mineral density (Figure 2) and content (Bitto et al, 2009) over the methylprednisolone-treated group and showed comparable efficacy with the vehicle group. Genistein co-administered with methylprednisolone also statistically maintained femoral bone's resistance to rupture compared with the methylprednisolone group ( Figure 3C) and preserved the normal architecture of cartilage as well as both cortical and trabecular bones with a well-organized matrix in femoral head (Figure 3 A and B).…”
Section: Evidence From In Vivo Studiesmentioning
confidence: 85%
“…Once osteonecrosis occurs, glucocorticoids also cause inhibition of bone regeneration (Takano-Murakami et al, 2009). In a rat model, we studied genistein preservative effects on methylprednisolone-induced bone loss and osteonecrosis of the femoral head (Bitto et al, 2009). In our study (Figure 1), genistein succeeded in preventing osteoporosis and osteonecrosis of the femoral head when co-administered with the glucocorticoid.…”
Section: Evidence From In Vivo Studiesmentioning
confidence: 99%
“…However, the therapeutic use of GCs in the management of immunosuppression following organ transplantation or of inflammatory diseases is always accompanied by substantial adverse outcomes including diabetes and obesity as well as bone loss, which is referred to in this case as GC-induced osteoporosis (GIOP) (3)(4)(5). Bone loss induced by GCs occurs early and progresses at a fast rate becoming significant within the first 6 months (6). Previous studies have demonstrated that the long-term administration of GCs resulted in the development of osteoporosis in approximately 50% of patients with asthma (7).…”
Section: Introductionmentioning
confidence: 99%